Meningkatkan Kinerja Kepala MAN Model Kota Sorong Melalui Metode Self Assesment (Penilaian Diri Sendiri) - Ramli, Muhammad (Al-Riwayah : Jurnal Kependidikan, 2020)
This study aims to determine the increasing of the Head master of MAN Model performance in City of Sorong through the Self-Assessment Method. This type of research is a supervisory action research conducted a participatory collaborative manner between the Head master of MAN Model Sorong as the Research Subject and the School Supervisor at Madrasahs as Researchers. The research was conducted in two cycles, each cycle consisting of four components, namely planning, acting, observing, and reflecting. Data collection techniques used in this study were interviews, observation, documentation, and data analysis. Data analysis was carried out in 3 stages, namely reduction, data presentation, and drawing conclusions. The results showed that: (a) the use of the Self Assessment method can improve the performance of the Head master of MAN Model Sorong. The increasing of the performance can be seen from the components of the Personality Standards in cycle 1 by 90%, increasing to 94% in cycle 2 or up by 4%. The Managerial Competency Standard in cycle 1 was 70% increased to 84% in cycle 2 or increased by 14%. The Entrepreneurship Competency Standard in cycle 1 was 88%, increasing to 93% in cycle 2 or increasing by 5%. The competency standards for supervision in cycle 1 were 78%, increasing to 86% in cycle 2 or increasing by 8%. The Social Competency Standard in cycle 1 was 67% increased to 80% in cycle 2 or increased by 13%. (b) The use of Self Assessment (Self-Assessment) can improve the performance of the Head master of the MAN Model Sorong with an average of 78% in cycle 1 increasing to 88% in cycle 2 or an increase of 10%.